2017
DOI: 10.1186/s13046-017-0620-3
|View full text |Cite
|
Sign up to set email alerts
|

PTEN expression is upregulated by a RNA-binding protein RBM38 via enhancing its mRNA stability in breast cancer

Abstract: BackgroundPTEN (phosphatase and tensin homolog gene on chromosome 10), a well-characterized tumor suppressor, is a key regulator of the phosphatidylinositol-3-kinase (PI3K)/AKT pathway involved in cell survival, metastasis and cell renewal. PTEN expression is closely related to the phenotype, prognosis and drug selection in breast cancer. It is mainly regulated by transcriptional and post-transcriptional modifications. RNA binding motif protein 38 (RBM38), an RNA-binding protein (RBP) and a target of P53 famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…differential INSR splicing in molecular subtypes of BC cells and affects cell aggressiveness [12]. And RNAbinding protein RBM38 increases PTEN expression via enhancing its mRNA stability in BC [13].Those studies along with ours indicate that lncRNAs are critical regulators for trastuzumab resistanceby binding with RBPs.…”
supporting
confidence: 66%
“…differential INSR splicing in molecular subtypes of BC cells and affects cell aggressiveness [12]. And RNAbinding protein RBM38 increases PTEN expression via enhancing its mRNA stability in BC [13].Those studies along with ours indicate that lncRNAs are critical regulators for trastuzumab resistanceby binding with RBPs.…”
supporting
confidence: 66%
“…For example, Nujiangexathone A suppresses cell growth by targeting HNRNPK in cervical cancer 31 . DAB2IP depletion facilitates cell metastasis in colorectal cancer by translocating HNRNPK into the nucleus and activates MMP2 transcription 32 . Our study demonstrated that HNRNPK could bind with circ‐0075804 and positively regulated the E2F3 expression in RB.…”
Section: Discussionmentioning
confidence: 67%
“…7,10,22,[50][51][52] RBM38 encodes an RNA-binding protein and a reported tumor suppressor that modulates gene expression by binding to adenylate-uridylate/uridylate-rich elements in the 39 untranslated region of target transcripts. [53][54][55] Of interest, murine Rbm38 deficiency promotes accelerated aging and lymphomagenesis, in part by destabilizing PTEN transcripts and decreasing PTEN protein expression. 55,56 In 17% of analyzed cHLs, there are previously unreported truncating or missense mutations of RBM38 ( Figure 1A,D).…”
Section: Ccgs In Chlsmentioning
confidence: 99%